Regulation of innate immunity by liquid–liquid phase separation: a focus on veterinary viruses - Zhou, Zibo; Yuan, Qingyang; Fan, Kewei; Huang, Teng (Frontiers in Microbiology, 2025)
For most pathogenic viruses, maintenance of their active life cycles requires a diverse array of strategies that efficiently mobilize the limited resource from host cells. Intriguingly, it remains elusive on how the essential building blocks are recruited and assembled to produce a large number of infectious virions within a crowded intracellular compartment, while the host innate immune constituents are deliberately excluded from this viral niche. Recently, emerging evidence has suggested that the intricate interplay between host and virus can invariably be modulated by a general physicochemical basis, known as liquid–liquid phase separation (LLPS). This mini-review outlines the mechanisms underlying LLPS that regulate the animal virus replication and finetune the innate immune signaling network, with a particular focus on manipulation of LLPS by veterinary viruses to antagonize the host innate immunity. With increased understanding of how viruses hijack LLPS for their persistence and immune evasion, more effective and targeted antivirals or therapeutics will be developed to prevent the enormous losses of domestic animals caused by viral infections.